Determinant Factors of Local Government Financial Performance (Using Financial Condition Dimension as Indicator) - Rahayu Lestari; Ahmad Nurkhin (Indonesian Management and Accounting Research, 2021)
The Research purpose is to examine the effect of determinan factors, which include government size, Intergovernmental revenue, capital expenditure, Population, and local tax revenue in influencing the local government financial performance with financial condition as proxy. The study Population is district and city government in Central Java The sample was taken by using purposive sampling technique, so we have 105 observation units. Data analysis used panel data multiple regression analysis with Eviews 12. The results showed that governmental size, capital expenditure and local tax revenue have a positive significant effect on the financial performance of local governments. Meanwhile, intergovernmental revenue and population negatively affect the financial performance of local governments. There is a negative effect of population due to the growth of population is not proportional to the improvement in regional financial conditions, thus reducing financial performance.